2015
DOI: 10.1080/14689367.2014.1001722
|View full text |Cite
|
Sign up to set email alerts
|

The non-smooth pitchfork bifurcation: a renormalization analysis

Abstract: We give a renormalization group analysis of a system exhibiting a non-smooth pitchfork bifurcation to a strange non-chaotic attractor. For parameter choices satisfying two specified conditions, self-similar behaviour of the attractor on and near the bifurcation curve can be observed, which corresponds to a periodic orbit of an underlying renormalization operator. We examine the scaling properties for various parameter choices including the so-called pitchfork critical point. Finally, we study the autocorrelati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(11 citation statements)
references
References 16 publications
2
9
0
Order By: Relevance
“…The work also provides a link between the two-level system and other quasi-periodically forced systems. We have shown that the renormalization strange set occurring for symmetric barrier billiards can be reproduced in the two level system, and in [1] we found the same set occurring in the study of correlations of strange non-chaotic attractors, thus making it a somewhat universal set in the study of correlations for this class of system. This work can be trivially generalised to a class of quadratic irrational frequency as has been done in the past [15], although the problem of generalising to general irrational frequencies remains challenging.…”
Section: Resultssupporting
confidence: 67%
See 2 more Smart Citations
“…The work also provides a link between the two-level system and other quasi-periodically forced systems. We have shown that the renormalization strange set occurring for symmetric barrier billiards can be reproduced in the two level system, and in [1] we found the same set occurring in the study of correlations of strange non-chaotic attractors, thus making it a somewhat universal set in the study of correlations for this class of system. This work can be trivially generalised to a class of quadratic irrational frequency as has been done in the past [15], although the problem of generalising to general irrational frequencies remains challenging.…”
Section: Resultssupporting
confidence: 67%
“…In future works we hope to be able to produce an analytic proof of the chaoticity of the correlations for symmetric barrier billiards (which lie on the set shown in Figure 4) by conjugating the renormalization operator to a sub-shift of finite type. If successful, this will naturally carry over to the work presented here for the two-level system and Figure 15: Renormalization strange set which appears in the limit κ → 0. the work presented in [1] for the correlations of SNAs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The models under consideration are 'pinched skew-products' (a term used by Glendinning in [6]), and undergo a transition to SNA at a critical parameter value via the non-smooth pitchfork bifurcation which we have previously studied in [1]. The work in [1] was motivated by [14], in which the bifurcation was labelled 'the blow-out birth' of an SNA.…”
Section: Introductionmentioning
confidence: 99%
“…The models under consideration are 'pinched skew-products' (a term used by Glendinning in [6]), and undergo a transition to SNA at a critical parameter value via the non-smooth pitchfork bifurcation which we have previously studied in [1]. The work in [1] was motivated by [14], in which the bifurcation was labelled 'the blow-out birth' of an SNA. In both papers a renormalization approach is presented and scaling properties of the attractor both at and near the critical point of transition are determined showing its self-similarity for certain choices of initial phase.…”
Section: Introductionmentioning
confidence: 99%